2023
DOI: 10.1021/acs.iecr.3c01364
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Effective Density for the Separation of Immersed Objects in the Gas–Solid Fluidized Bed Coal Beneficiator

Abstract: Effective density for the separation of immersed objects which determines the performance of coal dry beneficiation is of primary importance for Gas−Solid Fluidized Bed Coal Beneficiator (GSFBCB) applications. Of all factors affecting the effective density, fluidization hydrodynamics and properties of medium particles and immersed objects play the dominant roles. By correlating all available experimental data found in the literature, a general correlation has been developed for the first time to predict the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Immersed objects in fluidized beds have received considerable attention in recent studies, highlighting their critical role in influencing bed dynamics and reactor performance [22]. Researchers studied a variety of immersed objects, ranging from static internals, such as baffles [23] and heat exchangers [24], to dynamic elements, like moving packings [25] and disks [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immersed objects in fluidized beds have received considerable attention in recent studies, highlighting their critical role in influencing bed dynamics and reactor performance [22]. Researchers studied a variety of immersed objects, ranging from static internals, such as baffles [23] and heat exchangers [24], to dynamic elements, like moving packings [25] and disks [26].…”
Section: Introductionmentioning
confidence: 99%
“…For example, static internals are often used to enhance mixing, reduce bubble size, and improve heat transfer efficiency, while dynamic elements can induce more complex hydrodynamic behavior [27]. The interaction between these objects and the particulate phase was shown to be critical in optimizing reactor conditions for specific processes, such as combustion [28], gasification [22], and chemical looping [28]. In this study, we focused on evaluating the effect of different moving internals on fluidized bed hydrodynamics, exploring configurations in vertical, inclined, and rolling orientations.…”
Section: Introductionmentioning
confidence: 99%
“…The on-site monitoring results showed that the regenerated form of the FCC unit has the greatest impact on CH 4 , and CO 2 is the primary GHG, with total emissions of >99%, and coke content and composition on the spent catalysts can directly affect GHG emissions . Fu et al developed a general correlation to predict the effective density for immersed object separation in fluidized beds, and the proposed correlation not only provides an efficient mechanism for the design and operation of a Gas–Solid Fluidized Bed Coal Beneficiator (GSFBCB) for coal dry beneficiation, but also is applicable for iron and copper ore pretreatment, agricultural crop cleaning, municipal solid waste classification, etc. A pseudo-Siamese neural network-based moisture classification method for fused data was proposed by Chen et al, when the effect of moisture of solid particles on changes in flow motion and flow field was explored.…”
mentioning
confidence: 99%